The Moral Work of Subversion - Paul White (Human Relations, 2016)
This paper engages critically with dominant understandings of morality and subversion within organizations and through a close examination of existing organisational literature. We show how contemporary organisational literature fails to adequately adequately address the ways in which a given 'morality' produces and justifies everyday subversive practices an the means through which it legitimates and stabilises already existing power relations within organisations. Developing work from interactionist sociology, we highlight the means through which subversion legitimates the diverse range of actions performed by organizational subjects through processes of post hoc rationalisation. This rationalisation is of itself a particular form of retrospective reasoning referred to as ‘moralization’, which forms a resource for subjects to actively negotiate the often competing moral and practical demands placed on them as organizational subjects. Subversion, within our analysis represents an important means of accomplishing, legitimating and preserving a given organizational order, rather than assume subversion necessarily subverts organizational values. It is through a close analysis of organisational and theoretical literature that we show the ‘positive’ function of rule-bending for enabling and sedimenting processes of organizational control.